Prekyba Lietuvoje viešpataujant naciams - Braslauskas, Justinas (Lietuvos istorijos studijos, 2001)
Trade organisation in Lithuania during occupation by the Nazis was stimulated not by the country’s local economy development but by an exterior factor - the intention of Germany, the aggressor state, to gradually integrate the local economy into its own economy. It was obviously demonstrated by the establishment of German companies in the region as well as by giving most of the wholesale and larger-scale retail businesses at those companies’ disposal. In spite of the fact that it was permitted to re-privatise the smaller retail businesses which had been nationalised by the Soviet power, both retail and wholesale trade in Lithuania during the Nazis’ occupation was moribund due to the scarcity of goods and transport and unworkable wage and price policy. In comparison with 1941, the number of retailers decreased by one fourth. In the region, the illegal and barter trade became especially widespread. The policy of subjugation of Lithuania’s trade to the needs of the Reich was softened by the Lithuanian administration that was left to function alongside the German occupying civil authorities. Only on the initiative of officers of this administration were there new trade schools founded, various training and refresher courses for traders organised.